Pengaruh Pemberian Jus Nanas Terhadap Penurunan Kadar Asam Urat pada Lansia di RT 05 RW 06 Kelurahan Rempoa Kecamatan Ciputat Timur Kota Tangerang Selatan - Fika Ayu Barokah; Gaung Eka Ramadhan (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Gout purine metabolism disorder if it does not last normally, there will be a process of accumulation of crystals of uric acid in the joints and cause pain. This condition is commonly found in the elderly due to the slow rate of metabolism of the body. The prevalence of gout or gout based on diagnosis of health workers in Indonesia (7.3%) and based on the diagnosis or symptoms (24.7%). The purpose of this study was to determine the effect of pineapple juice on reducing uric acid levels in the elderly. This research design uses a quasi-experimental with one group pretest- posttest without control. The population in this study was 22 elderly with 18 samples who’s experienced with high level of uric acid. This study used sampling technique with was purposive sampling. The test results of this study found that the average before pineapple juice intervention was 8,244 mg/dl, after pineapple juice intervention was 6,628 mg/dl, and the final results of the paired T test showed that the p value was 0.000 (α≤ 0.05) so it could be concluded that there was an effect of giving pineapple juice on reducing uric acid levels in the elderly. This means that H0 is rejected and Ha is accepted. From the results of this study, it is hoped that it can be considered as one of the nursing care interventions by providing education in reducing uric acid levels as a source of useful information for the community